Peranan Strategi Pembelajaran Contextual Teaching And Laerning Pada Mata Pelajaran Fiqih - Arlina Arlina; Nurul Afriliani Gajah; Mawaddatu Shifa; Fathis Silmi Ramadhani; Khoirun Nisa Manungkalit (Politeknik Kampar, 2023)
This study discusses learning Fiqh in the CTL (Contextual Teaching and Learning) learning method with a learning concept that helps teachers relate the material taught to students' real-world situations and encourages students to make connections between the knowledge they have and its application in their lives as family members and public. This article uses the content analysis research method. Content analysis is a research method used to understand the meaning of written text, images, or audio in certain contexts. This method is carried out by identifying and categorizing information contained in text or images, then interpreting the meaning contained therein. The results of the study show that the learning strategy of Contextual Teaching and Learning in the Subject of Fiqh plays a very important role for students and is also increasingly motivated to participate in learning and is able to solve all the problems encountered, both problems that are found directly during the learning process and when solving evaluation questions that are given, then the overall results of this study indicate that the model of applying the CTL (Contextual Teaching and Learning) strategy with the cooperative learning method is able to increase student activity and mastery of concepts of learning material and is very suitable to be applied to train students' abilities to find, associate previous material with studied material.